On the Relationship between Addiction and Social Security In Urban Community - nasrin danaei (Drug Control Headquarters, Research and Education Office, 2016)
Objective: This paper is an attempt to explain the relationship between social factors and tendency to addiction and determine the relationship of this tendency with social insecurity. In addition, the contribution of each of the social factors that lead to social insecurity is determined. Method: The current research method is descriptive. At first the relationship between the research indices (family, neighborhood, unemployment, etc.) and tendency to addiction was described. Then, the relation of this tendency with social insecurity has been expressed. In the following, the contribution of each of these factors in the estimation of social insecurity has been determined. Results: The results showed that the indices under study are significantly correlated with tendency towards addiction and social insecurity. The most important predictors of social insecurity were respectively as follows: other factors (extent of border with Pakistan and Afghanistan, international and regional trafficking activities, the booming market of drugs, etc.), anomic situation, industrialization, family, friends and peers, access to drugs, unemployment, and finally neighborhood. Conclusion: Such variables as family, neighborhood, friends and peers, anomic situation, access to drugs, industrialization, and unemployment play a significant role in social security.